1996
DOI: 10.1063/1.871729
|View full text |Cite
|
Sign up to set email alerts
|

Experimental observations and simulations on relativistic self-guiding of an ultra-intense laser pulse in underdense plasmas

Abstract: The experimental images of the sidescattered light from a plasma, created by the multiterawatt laser pulse propagating in a hydrogen gas jet, exhibit clear dependence on both gas jet pressure and laser power. Two-and three-dimensional simulations of wave propagation, in presence of the relativistic electron mass increase and the ponderomotive expel of electrons, have been performed to reproduce the Thomson radiation from the plasma electrons. They show electron cavitation induced by the beam focusing, self-foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 62 publications
0
24
0
Order By: Relevance
“…2 (top), it can be explained in terms of pulsation regime of self-guided propagation. 29 In this regime, the scattering efficiency decreases with periodical reduction of the scattering volume and local electron density. It is a typical self-modulation instability.…”
Section: Discussion and Numerical Simulationsmentioning
confidence: 99%
“…2 (top), it can be explained in terms of pulsation regime of self-guided propagation. 29 In this regime, the scattering efficiency decreases with periodical reduction of the scattering volume and local electron density. It is a typical self-modulation instability.…”
Section: Discussion and Numerical Simulationsmentioning
confidence: 99%
“…This effect has been shown to have a power threshold given by P c 16.5n c ͞n e ͓GW͔, where n c is the critical density (when v p v 0 ) [4]. Recent simulations [13] have shown that this effect has different properties, depending on the laser power. At the critical power threshold, only the focal intensity increases.…”
Section: Electron Acceleration By a Laser Wakefield In A Relativisticmentioning
confidence: 99%
“…This is consistent with the strong blueshifting we observe in the scattered spectra. Even though simulations indicate that the laser focuses to ϳ2 mm [13], the complex dynamics that occur as the laser continually focuses and defocuses in the plasma make it impossible to determine the minimum self-focused beam width from the far field divergence angle.…”
Section: Electron Acceleration By a Laser Wakefield In A Relativisticmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, a channel with a radially parabolic density profile of the form n(r) = n 0 + ∆nr 2 /r 2 0 can guide a Gaussian laser pulse with a constant spot size r 0 provided the channel depth ∆n satisfies ∆n = ∆n c , where ∆n c = 1/πr e r 2 0 is the critical channel depth [4] and r e = * Work supported by the U.S. . Plasma channels have been created in the laboratory by a variety of methods: (i) Passing a long laser pulse through an optic to create a line focus in a gas, which ionizes and heats the gas, creating a radially expanding hydrodynamic shock [1,[5][6][7][8][9][10][11], (ii) using a slow capillary discharge to control the plasma profile [12], and (iii) using the ponderomotive force of an intense, relativistically self-guided laser pulse in a plasma, which creates a channel in its wake [13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%